2001
DOI: 10.1046/j.0960-7692.2001.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery Doppler and placental volume in the first trimester in the prediction of pregnancy complications

Abstract: The combination of placental volume measurement and uterine artery Doppler in the first trimester may identify women at risk for subsequent development of pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 7 publications
9
53
0
4
Order By: Relevance
“…(19,20) similarly our study demonstrated three and a half and three-fold increase in risk in developing preeclampsia and IUGR. Our study has results which are comparable with one of the largest study of Martin et al 14 It has been studied that placental ischemia and infarcts, which is a result of defective placentation is the basis behind severe form of early onset preeclampsia or IUGR.…”
Section: Discussionsupporting
confidence: 77%
“…(19,20) similarly our study demonstrated three and a half and three-fold increase in risk in developing preeclampsia and IUGR. Our study has results which are comparable with one of the largest study of Martin et al 14 It has been studied that placental ischemia and infarcts, which is a result of defective placentation is the basis behind severe form of early onset preeclampsia or IUGR.…”
Section: Discussionsupporting
confidence: 77%
“…Many other studies have shown similar results. [15][16][17][18] In the present study, a large proportion of women who were predisposed to developing PE could be predicted. However there is still a lot of scope for increasing the detection of PE.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, 16 cases (16%) had Mean PI ≥ 2.00 (90 th centile) and this group contained 8 cases (36.4%) of those that developed IUGR and Pre-eclampsia similar to the study conducted by Schuchter K et al in which uterine artery PI was ≥90th centile in 38 (10%) pregnancies and this group contained nine (25%) of those that developed complications. 20 Mean UtA PI was significantly higher (p value <0.05) in Pre-eclamptic cases that required delivery before 34 weeks thus, much better at identifying the more severe and clinically most relevant cases of Pre-eclampsia. Papaqeorqhiou AT et al reviewed the previous studies which showed that for a false positive rate of 5%, firsttrimester uterine artery Doppler studies will detect 50-65% of women who will develop severe preeclampsia.…”
Section: Discussionmentioning
confidence: 98%